The maternalists psychoanalysis, motherhood, and the British welfare state - Bar-Haim, Shaul (Intellectual history of the modern age., 2021)
"This book discusses the role of motherhood in psychoanalysis, and how this contributed to the British welfare state in the first half of the twentieth century"--